Asosiasi antara Intensitas Alokasi Dana Desa dengan Ketimpangan Pendapatan dan Akses Air Bersih (SDG 6.1) Di Indonesia: Aplikasi Continuous Difference-In-Differences (2015-2022) - Wildan Maulana Assani Mualim; Adhimas Krisnaya Arrasya; Muhammad Fachriansyah; Muhammad Atha Devanta; Arina Romarina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Income inequality and unequal access to safe drinking water remain persistent challenges in Indonesia’s rural development agenda, despite substantial fiscal transfers through the Village Fund Program since 2015. This study aims to examine how variations in Village Fund allocation intensity influence income inequality and access to safe drinking water (SDG 6.1) across 514 districts from 2015 to 2022. Using a continuous difference-in-differences framework, the analysis integrates panel data from the Ministry of Villages, the Central Bureau of Statistics, and the World Bank, while controlling for demographic, fiscal, and policy heterogeneity. The findings indicate that a one-standard-deviation increase in per-capita Village Fund allocation is associated with a 0.015-point reduction in the Gini coefficient and a 0.26-percentage-point increase in access to safe drinking water. Although the magnitudes are modest, the effects are statistically significant and stronger in regions with higher institutional capacity. These results highlight the need for improved targeting, institutional strengthening, and cross-sectoral coordination to enhance the Village Fund’s contribution toward inclusive and sustainable development.